2022
DOI: 10.1155/2022/5005747
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of NXPH4 Correlates with Immune Cell Infiltration and Unfavorable Prognosis in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the leading malignant carcinomas. Despite the advancement in the treatment for HCC, such as precise hepatectomy, radiotherapy, transarterial therapies, chemotherapy, targeted treatments, and immunotherapy, the 5-year overall survival rate of HCC is extremely low. Hence, novel biomarkers are urgently needed for advancing the therapy and prognosis of HCC. Neurexophilin 4 (NXPH4) is a neuropeptide-like glycoprotein. The study is designed to investigate the function of NXPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Emerging evidence highlights the role of immune cell infiltration in the development, metastasis, and antitumor therapies of COAD ( 55 ). NXPH4 has been reported to play a role for the immune infiltration in bladder cancer ( 11 ) and hepatocellular carcinoma ( 14 ). Our analysis revealed that upregulated NXPH4 expression associates with increased infiltration of various immune cell types including NK cells, NK CD56bright cells, cytotoxic cells, macrophages, aDC cells, Th1 cells, neutrophils, and Treg cells in COAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence highlights the role of immune cell infiltration in the development, metastasis, and antitumor therapies of COAD ( 55 ). NXPH4 has been reported to play a role for the immune infiltration in bladder cancer ( 11 ) and hepatocellular carcinoma ( 14 ). Our analysis revealed that upregulated NXPH4 expression associates with increased infiltration of various immune cell types including NK cells, NK CD56bright cells, cytotoxic cells, macrophages, aDC cells, Th1 cells, neutrophils, and Treg cells in COAD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have also implicated NXPH4 in the development and progression of several malignant tumors including bladder cancer ( 11 - 13 ), hepatocellular carcinoma ( 14 , 15 ), and non-small cell lung cancer ( 16 ). Additionally, it was reported that NXPH4 promotes gemcitabine resistance in bladder cancer ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of NXPH4 in cancer has only recently been investigated. NXPH4 shows a higher expression level in LIHC, BLCA, and non-small cell lung cancer [ 16 , 17 , 27 ], but the cause of NXPH4 dysregulation remains unclear. Our study also revealed a higher NXPH4 expression level in the transcriptome of most cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies in peripheral blood are needed to translate the diagnostic potential of NXPH4 into clinical application, and NXPH4 also has the potential to serve as a prognostic marker. In BLCA and LIHC, NXPH4 was associated with a worse prognosis [ 17 , 27 ]. The findings of this research validate previous research and analyze the link between NXPH4 and OS, DSS, and PFS in pan-cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Neurexophilin 4 (NXPH4) is a synaptic secretory protein belonging to the NXPH family. Recent studies have revealed that NXPH4 is highly expressed in bladder cancer ( 6 ), liver cancer ( 7 ), breast cancer ( 8 ) and several other types of cancer. A previous study showed that NXPH4 knockdown can inhibit cell proliferation and migration, leading to significant cell cycle stagnation at the S1 stage in non-small cell lung cancer cells ( 9 ).…”
Section: Introductionmentioning
confidence: 99%